1996
DOI: 10.1017/s0960258500003147
|View full text |Cite
|
Sign up to set email alerts
|

Development of a thermal time model for the quantification of dormancy loss in Aesculus hippocastanum seeds

Abstract: The effects of temperature on dormancy loss, germination and viability were investigated in seeds of Aesculus hippocastanum L. harvested over a 4-year period. Release from embryo dormancy in freshly harvested seeds was manifest in two phases of morphological growth: initially, when the seed lot was only partially released, axis emergence resulted primarily from cotyledonary petiole extension without radicle extension; subsequently, when the seed lot was totally released, axis emergence of all seeds was followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 25 publications
1
45
0
Order By: Relevance
“…The soil temperature data were also used to calculate the accumulation of chill units to determine the quantity of dormancy-breaking chilling that was available after each sowing date. The exact temperature response for dormancy breakage of ash and sycamore seed is unknown, but published studies on other deeply dormant species (Seeley and Damavandy, 1985;Pritchard et al, 1996) show that dormancy is broken most rapidly at temperatures between 0 and 5 8C, with effectiveness decreasing at warmer temperatures. In this study, temperatures between 0 and 5 8C were assumed to be equally effective at accumulating a chill unit for every hour's exposure, the rate of accumulation was proportionately decreased to zero as temperatures increased from 5 to 10 8C (no soil temperatures below 0 8C were recorded in this study).…”
Section: Laboratory Germination Data and Thermal Time Estimationmentioning
confidence: 99%
“…The soil temperature data were also used to calculate the accumulation of chill units to determine the quantity of dormancy-breaking chilling that was available after each sowing date. The exact temperature response for dormancy breakage of ash and sycamore seed is unknown, but published studies on other deeply dormant species (Seeley and Damavandy, 1985;Pritchard et al, 1996) show that dormancy is broken most rapidly at temperatures between 0 and 5 8C, with effectiveness decreasing at warmer temperatures. In this study, temperatures between 0 and 5 8C were assumed to be equally effective at accumulating a chill unit for every hour's exposure, the rate of accumulation was proportionately decreased to zero as temperatures increased from 5 to 10 8C (no soil temperatures below 0 8C were recorded in this study).…”
Section: Laboratory Germination Data and Thermal Time Estimationmentioning
confidence: 99%
“…Consequently, the most simple explanation, that low temperatures relieve and high temperatures induce dormancy, must give way to more complex concepts of temperature control for dormancy changes. It may be concluded that threshold temperatures derived from germination at a single germination test condition are not sufficient to characterize the dormancy changes of a seed population in the field, or in the laboratory after application of a range of stratification temperatures ͑Pritchard et al 1996. It is conceivable that individual seeds have different limits for dormancy change and the use of static threshold temperatures for dormancy changes would therefore be problematic.…”
Section: Dormancy Relief Dormancy Inductionmentioning
confidence: 99%
“…In this study, the impact of assisted migration on regeneration and synchronisation with the seasons is assessed using thermal time models. Thermal time models have previously been developed for Q. robur (Pritchard and Manger 1990) but also for other recalcitrant species including Aesculus hippocastanum (Pritchard et al 1996(Pritchard et al , 1999 and Castanea sativa (Pritchard and Manger 1990). These have focussed on germination i.e.…”
Section: Introductionmentioning
confidence: 99%